Use of glazed ceramic waste as additive in mortar and the mathematical modelling of its strength - Altin, Zehra Gulten; Erturan, Seyfettin; Tepecik, Abdulkadir (SAGE PUBLICATIONS LTD, 2008)
This study investigated the reusability of waste material from the tile manufacturing industry as an alternative material to natural pozzolan trass. Yield strength values of mortar made from Portland cement (CEM I 42.5), were measured by adding glazed ceramic waste and trass at various weight ratios (5 to 40%). The test results proved that the strength values at 2, 7, and 28 days gave good results for concentrations of waste materials less than 5-10% in the cement. A decrease in strength was observed at higher concentrations. Mathematical modelling results showed a logarithmic correlation between the mortar strength and weight fraction of cement.
Keywords: glazed ceramic waste; pozzolan; cement; mortar additives; mathematical modelling; wmr 1175-1; SILICA FUME; CONCRETE; Engineering; Environmental Sciences & Ecology